Ari (Ediciones UC, 2017)
The Philosophy for Children Program, created in 1969 by Matthew Lipman, is widely recognized in the world for its significant impact on the academic excellence of children and adolescents, by fostering critical and creative thinking through the development of reading comprehension, logical reasoning and mathematician, dedication to work and motivation for knowledge. It has a notable effect on the development of self-esteem and promotes respect and tolerance. The narratives that we present in this series touch on themes of philosophy of all times and stimulate questions and reflection of children and young readers to invite them to a philosophical dialogue and, through the active guidance of the teacher, become an attractive tool. and extraordinarily effective in leading them to an ever-increasing level of understanding about themselves, their peers, society, and the world around them. Being distracted in class, Ari makes a mistake and, reflecting on it, discovers a rule of Aristotelian logic. Fascinated with his discovery, he manages to embark his friends and colleagues on a search for more rules and their application to everyday life situations. In his discussions they touch on topics as varied as art, culture, the meaning of education, religious tolerance, argumentative fallacies or the sense of belonging to a community.